(untitled) (Journal of Pharma Insights and Research, 2023)
UV spectroscopy, as one of the earliest instrumental techniques for analysis, has proven to be a versatile and indispensable tool in various scientific domains. Its capability to distinguish different types of materials makes it a valuable asset in analytical chemistry. This method is commonly employed to ascertain the identity, strength, quality, and purity of diverse samples. The fundamental principle of UV spectroscopy lies in the absorption of specific wavelengths of light by samples, and it provides valuable insights into the responses of substances to this absorption. The application of Beer’s law, a universal principle in UV spectroscopy, elucidates the absorption of radiant energy by samples. Notably, this method is characterized by its accuracy, simplicity, and a broad spectrum of applications, including drug discovery, structural elucidation of organic molecules, molecular weight determination, and the detection of impurities. Both quantitative and qualitative analyses can be conducted effectively using UV spectroscopy. The equipment operates within a wavelength range of 200nm to 800nm, allowing the analysis of both colorless and colored compounds in both the UV and visible regions. In summary, UV spectroscopy stands as a robust analytical technique with wide-ranging applications, making it a cornerstone in scientific research and analysis.